Curating in a time of ecological crisis : biennales as agents of change - Fenner, Felicity, 1962- (Abingdon, Oxon : Routledge, 2022)
"Curating in a Time of Ecological Crisis reaffirms the relevance and impactful role of art, revealing how contemporary art exhibitions can capture the zeitgeist and advance new and collaborative approaches to a more sustainable inhabitation of Earth. The book is largely focused on biennales, which it argues are the contemporary exhibition models with the greatest capacity to offer new perspectives and propose alternative ways of connecting with our social and natural environments. Fenner demonstrates this by showing how curators of these high-profile exhibitions are responding in creative and engaging ways to the issues that preoccupy artists and society more broadly, of which the ecological crisis is paramount. Drawing on case studies from different parts of the world, the author reveals how biennales can make a constructive contribution to debates and attitudes around climate change, and how the role of the curator has evolved to embrace a duty of care not just to art but to the natural world. Curating in a Time of Ecological Crisis investigates how large-scale exhibitions of contemporary international art can become agents of change. As such, the book will be essential reading for scholars, students and practitioners with an interest in exhibitions, curating, contemporary art and environmental sustainability"--
Exhibiting Nature through the Decades: From Earthworks (1968) to Down to Earth (2021) -- Critical Ecosystems: Biennales and new curatorial strategies in response to climate change -- Environment and Empowerment: Biennales as legacy projects.
OCLC-licensed vendor bibliographic record.
Keywords: Biennials (Art fairs) -- Social aspects; Curatorship -- Philosophy; Environmentalism in art; Environmental responsibility; ART / Collections, Catalogs, Exhibitions